The Effect of Listening Murrotal Al-Quran Surah Ar-Rahman on Menstrual Pain Scale - Mardiyanti, Ika; Anggraeni, Medyasa; Anggasari, Yasi; Zuwariyah, Nur; Ristanti, Adenia Dwi; Umamah, Faridah (International Journal of Psychosocial Rehabilitation, 2020)
Dysmenorrhea is often experienced by some women during menstruation. Few women cannot perform activities until they do drug therapy. Ef orts to overcome dysmenorrhea are pharmacological and non- pharmacological therapies. Murottal Al-Quran Surah Ar Rahman therapy as a non-pharmacological therapy with slow tempo and quiet rhythm will increase endorphin hormone so that the scale of pain will be reduced. The purpose of this study was to know the ef ect of listening therapy of Murottal Al-Quran Surah Ar-Rahman on the scale of menstrual pain. Research method used Pre-Experimental with One Group Pre-Test Post-Test Design. Sampling through simple random sampling method amount 31 respondents with a population of 34 respondents. Independent variable was listening therapy of Murottal Al-Quran surah Ar-Rahman. Dependent variable was menstrual pain scale (dysmenorrhea). The research instrument was using mp3 through handphone with headset, and numeric rating scale questionnaire. Data were analyzed by paired t-test with significance level α = 0,05. The research finding showed that prior to the treatment of Murrotal Al-quran Surah Ar-Rahman, the average of dysmenorrhea was on scale 4.29 (moderate pain) and after given by the treatment, average of dysmenorrhea was on scale 1.16 (mild pain). After paired t-test, gotten ρ value 0,000 and α = 0,05. Means ρ